The last Dalai Lama? [videorecording (DVD)] (Alive Mind, 2019)
A contemporary fresh look at what is truly important for the fourteenth Dalai Lama: The ongoing confrontation between Tibetans and China; His Holiness's influence in political and spiritual spheres; his work with educators and neuropsychologists; and his personal feelings on aging, dying and the question: Will there be a fifteenth Dalai Lama, or will he be the last.